The impact of physical exercise on primary school teachers’ professional ethics: the mediating role of self-control - Kequn, Chu; Xiuqing, Yang; Tinghui, Zhang (Frontiers in Psychology, 2025)
BackgroundPhysical exercise has been shown to positively impact psychological and behavioral outcomes, yet its influence on professional ethics in educators remains underexplored. Understanding the mechanisms underlying this relationship is essential for developing interventions to promote ethical behavior in educational contexts.ObjectivesThis study aims to investigate the relationship between physical exercise and professional ethics among elementary school teachers, with a specific focus on the mediating role of self-control.MethodsA sample of 380 elementary school teachers was recruited from Guangxi and Shandong provinces in China. Data on physical exercise, self-control, and professional ethics were collected using validated scales. Structural equation modeling (SEM) was employed to analyze the direct and indirect effects of physical exercise on professional ethics.ResultsThe findings revealed a significant positive correlation between physical exercise, self-control, and professional ethics. Self-control was found to partially mediate the relationship, with physical exercise having both a direct positive effect (β = 0.25, p < 0.01) and a stronger indirect effect (β = 0.50, p < 0.001) on professional ethics through self-control. The indirect effect accounted for 57.3% of the total effect.ConclusionThis study highlights the dual-pathway mechanism through which physical exercise enhances professional ethics, directly and indirectly via self-control. Practical implications include promoting physical activity and self-regulatory training as strategies to foster ethical behavior in educators. These findings provide a foundation for future research and interventions in educational settings.